Why road safety is the need of the hour? A study among youth of District Dehradun, Uttarakhand - Jain, Rajneesh; Vyas, Shaili; Semwal, Jayanti; Srivastava, Malini (Indian Journal of Community Health, 2019)
Background: Road traffic injuries are the eighth leading cause of death globally, and the leading cause of death for young people aged 15–29 years. Each year, almost 400,000 young people under 25 years old are killed in a road traffic crash - about 1049 youngsters every day. Aims and objectives: To find out the prevalence of road safety related health risk behaviours and its determinants amongst young males of District Dehradun. Methodology: It was a cross sectional study conducted over 12 months of duration. The study sample comprised of 1800 male youth aged 15-24years studying in various schools and colleges of District Dehradun. A pre-tested and pre-structured questionnaire (YRBSS) was used. The data was entered and analysed using SPSS-version 20.0. Results: Approximately three-fourth of youth reported never using seat-belt while driving and only 4.4% reported always using helmet whereas 24.0% accepted never use of helmet. Approximately one-fourth of the total 1168 at risk subjects in past 30 days, accepted driving a vehicle while drunk and 39.9% reported use of mobile phones while driving. Personality traits (extrovert, neuroticism and lack of direction) turned out to be the major factor in road safety related health risk behaviour. Conclusion: Although, road safety related health risk was found to be more among urban youth as compared to their rural counterparts, yet it was found alarmingly high for both rural and urban study population.